2006
DOI: 10.1002/pds.1340
|View full text |Cite
|
Sign up to set email alerts
|

Development of active safety surveillance system for traditional Chinese medicine: an empirical study in treating climacteric women

Abstract: This study demonstrates the effectiveness using active safety surveillance to document safety of TCMs. This surveillance system could probably be useful to document the safety of other alternative or complementary medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…When we carried out another clinical observation to monitor a new invented formula, TMN-1, it was found that five out of 203 adverse events were judged to be probably related to the treatment; these included three single events of nausea, abdominal pain, and abdominal fullness and two events of diarrhea over the 12-week therapy period (Table 1) [18]. Further analyses showed that TMN-1 treatment resulted in an inferior benefit among postmenopausal women, compared to the benefit obtained among women during the perimenopausal period [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When we carried out another clinical observation to monitor a new invented formula, TMN-1, it was found that five out of 203 adverse events were judged to be probably related to the treatment; these included three single events of nausea, abdominal pain, and abdominal fullness and two events of diarrhea over the 12-week therapy period (Table 1) [18]. Further analyses showed that TMN-1 treatment resulted in an inferior benefit among postmenopausal women, compared to the benefit obtained among women during the perimenopausal period [23].…”
Section: Resultsmentioning
confidence: 99%
“…An effective way of detecting TCM safety hazards is through active surveillance of a well-defined group of people who are taking the medication, who are then followed using the guidelines of GCP (good clinical practice) [18]. First we organized at the beginning of study design an expert focus group composed of practicing TCM doctors to determine if they had noticed any adverse events (AEs) associated with the treatment of subjects with a specific health condition.…”
Section: Methodsmentioning
confidence: 99%
“…Co-prescriptions of two or more herbal formulae such as Jia-wei-xiao-yao-san with Qiju-di-huang-wan, or with Liu-wei-di-huangwan, or with Gan-mai-da-zao-tang have not been recommended in ancient Chinese medicine textbooks, which raises concern for both their safety and effectiveness. Some adverse drug reactions, such as abdominal pain, diarrhea, pruritus, etc., were detected in a clinical trial which used three herbal formulae together for menopausal syndrome 18 . Thus, more outcome research is needed to test the effectiveness and safety of new prescription patterns of FHP.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional medicines are currently undergoing scrutiny to evaluate their effectiveness and to monitor their adverse effects (Normile 2003, Hsieh et al 2006. The active ingredients used in many traditional medicines are potentially toxic, often containing dangerous elements, and they may include heavy metals (Garnier andPoupon 2006, Palombo 2006).…”
Section: Lack Of Standardization On Quality Efficacy and Safetymentioning
confidence: 99%